2022
DOI: 10.1021/acsaem.1c04097
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the Critical Role of Oxidants and Additives in Doped Spiro-OMeTAD toward Stable and Efficient Perovskite Solar Cells

Abstract: Chemical dopants are often required in organic hole transport materials (HTMs) to enhance the film conductivity and power conversion efficiency (PCE) of solar cells. Although additives (LiTFSI + tBP) and oxidants (FK209) are key dopants in HTMs, their hygroscopic and volatile nature induce severe morphology change, ion accumulation, as well as perovskite corrosion, which significantly hinder PSC stability. Various dopant structures and compositions have been developed, but challenges remain in fundamentally un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 39 publications
0
31
0
Order By: Relevance
“…The conductivity of these films was examined by recording the I−V curves of devices with the configuration FTO/CsBi 3−x Sb x I 10 (Figure 2d). Clearly, CsBi 2.7 Sb 0.3 I 10 showed a much higher conductivity compared to CBI, indicating faster charge separation in the CsBi 2.7 Sb 0.3 I 10 film, 30,31 which will be beneficial for increasing the charge collection efficiency in devices. 32 To examine the changes of the surface morphology of perovskite films, scanning electron microscopy (SEM) was performed for CBI and Sb-doped films.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The conductivity of these films was examined by recording the I−V curves of devices with the configuration FTO/CsBi 3−x Sb x I 10 (Figure 2d). Clearly, CsBi 2.7 Sb 0.3 I 10 showed a much higher conductivity compared to CBI, indicating faster charge separation in the CsBi 2.7 Sb 0.3 I 10 film, 30,31 which will be beneficial for increasing the charge collection efficiency in devices. 32 To examine the changes of the surface morphology of perovskite films, scanning electron microscopy (SEM) was performed for CBI and Sb-doped films.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…[20][21][22] Indeed, Seo et al demonstrated that replacing the Li + in favor of Zn + improves the stability of the spiro-OMeTAD when illuminated over a period of 600 h. [21] Similarly, copper salts including cuprous thiocyanate, cuprous iodide, FK102 and FK209 amongst other copper (II) salts, have been frequently used on their own or as a co-dopant additive with LiTFSI to oxidize spiro-OMeTAD. [6,23,24] Recently, Zhu et al identified that by using FK209, arguably the most common copper-based additive, as a sole p-type dopant, the stability of spiro-OMeTAD could be improved via enhancing the morphology and hydrophobicity. This observation has been frequently reported in copper-based spiro-OMeTAD dopants.…”
Section: Introductionmentioning
confidence: 99%
“…This observation has been frequently reported in copper-based spiro-OMeTAD dopants. [6,23,24] However, for optimal hole conduction and subsequent device performance, LiTFSI is required as a co-dopant. In this context, developing strategies that can be easily integrated to improve the long-term stability of the LiTFSI-doped spiro-OMeTAD devices whilst also maintaining high PCEs is essential and a practical choice.…”
Section: Introductionmentioning
confidence: 99%
“…Longer τ n means a slower recombination process, which is beneficial for a higher charge collection efficiency. [ 58 ] The longer τ n for the devices with KSCN‐PEO compared with the other devices could be mostly associated with the high‐quality perovskite film in terms of crystallinity, conductivity, uniformity, and defect density. To further understand the charge recombination mechanism, we carried out V oc versus light intensity measurements.…”
Section: Resultsmentioning
confidence: 99%